Pengaruh Likuiditas, Profitabilitas, Leverage, dan Good Corporate Governance Terhadap Financial Distress - Savitri, Erika Dian; Nursiam (Jurnal EMT KITA, 2024)
This study aims to analyze the effect of profitability, profitability, leverage, and good corporate governance on financial distress. This study is quantitative research. Quantitative Data obtained by using secondary data in the form of documentation of financial statements obtained through www.idx.co.id. This study will be proven by testing the hypothesis using statistical analysis methods with multiple linear regression analysis assisted using SPSS applications. The population used in this study is food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2022. The sampling method used in this study was purposive sampling. The results provide empirical evidence that liquidity, profitability, and independent commissioners have no effect on financial distress, while leverage, and managerial ownership influence financial distress.